STRATEGI KEPALA SEKOLAH DALAM PENGUATAN KARAKTER GURU DAN PEMBENTUKAN KARAKTER SISWA DI SMK ISLAM TASTURA AZZIRA MANGKUNG - Sahirjan, Lalu (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2025)
The lack of strong character among teachers and students at SMK Islam Tastura Az-Zikra Mangkung necessitates the need for effective principal strategies in character strengthening. This research aims to describe the principal's strategy in strengthening teacher character and building student character, as well as to identify supporting and inhibiting factors. The research employed a descriptive qualitative approach using observation, interview, and documentation techniques. Data analysis involved data reduction, data presentation, and conclusion. The research findings indicate that teacher character-strengthening strategies encompass workshops, motivation and rewards, team collaboration, standardization, habituation, as well as professional development. Student character-building strategies include the development of religious values, discipline, and environmental awareness. Supporting factors include teacher and student self-awareness, leadership support, availability of facilities and infrastructure, and family cooperation. Inhibiting factors include low personal commitment, miscommunication, limited teaching staff, parents' busy schedules, and limited access to information. This research provides practical contributions for principals in designing effective character-strengthening strategies